Market segment of families with children: a new stimulus for modern Czech spa industry? - Darina Jelínková; Zuzana Tučková; Zuzana Jurigová (Journal of International Studies)
The paper deals with a comprehensive range of hotel services for families with children at spa facilities of the Czech Republic, in line with current trends and requirements of this market segment. The main goal of this paper is to determine the preferences, needs and requirements of families with children in terms of amenities and services offer at spa hotels designated specifically for this target group. The secondary goal is to determine the current state of hotel services and facilities of Czech First Class hotels, which are the holders of the Baby Friendly Certificate. Subsequently, service offerings of these spa hotels are compared with the existing range of services for families with children in the selected Czech spas. In conclusion, based on the information obtained from the analyses and marketing research, a solution of the services portfolio intended for the market segment of families with children is recommended here using marketing mix as applied to tourism.